Early Cognitive Function after Deep Sedation Using Different Anesthetic Agents in Pediatric Patients: A Prospective, Randomized Controlled Trial - Min Suk Chae; Ji Yeon Kim; Hyun Jung Koh (Medicina, 2024)
Background and Objectives: The impact of anesthetic agents on memory and cognitive function following general anesthesia is of great interest, particularly regarding their effects on the developing pediatric brain. While numerous studies have examined the relationship between anesthetic drugs and brain function, research focusing on early cognitive function following sedation remains limited. Materials and Methods: This study was a prospective, randomized controlled trial involving 148 pediatric patients scheduled for hematological procedures, specifically bone marrow aspiration (BMA) and intrathecal chemotherapy (ITC). Patients were divided into two groups based on the primary anesthetic used: the inhalational sedation group (IHG), in which sevoflurane was used, and the intravenous sedation group (IVG), which received propofol infusion. Apart from the main anesthetic agent, all sedation methods were consistent across both groups. A cognitive function test administered before sedation involved memorizing four distinct images, each associated with a different number. Then, the patients were asked to identify the omitted image upon awakening in the recovery room. Herein, this pre- vs. post-sedation test is called the early recognition assessment (ERA) tool. The primary outcome was the correct response rate after sedation for the two groups. Secondary outcomes included the sedation score, the behavior response score, and the correct response rates according to the number of sedation procedures. Results: This study included 130 patients in the final analysis, with 74 originally assigned to each group. The initial cognitive assessment revealed no significant difference in performance between the anesthetic agents. In addition, no differences were observed in the rates of correct responses or post-sedation scores after repeated procedures. However, the IVG demonstrated higher behavior response scores compared to the IHG. Conclusions: There were no significant differences in the rates of correct responses using the ERA tool between the two groups, irrespective of the number of sedation procedures performed. While some differences were noted in preoperative, intraoperative, and post-anesthesia care, these did not significantly impact the cognitive outcomes measured.